101 techniques oil - Sanmiguel, David; Brunelle, Michael (Hauppauge, NY Barrons Educational Series, Inc., 2013)
A visual instruction guide that teaches all aspects of painting with oils.
Materials -- Diluted color -- Heavy body paint -- Modeling -- Brushwork -- Surfaces -- Color harmonies -- Light and shadow -- Execution and style -- Fillers and textures.
Keywords: Painting -- Technique